Perancangan User Interface Aplikasi Pemodelan Perangkat Lunak Menggunakan Metode User Centered Design - Egia Rosi Subhiyakto; Yani Parti Astuti; Liya Umaroh (Program Studi Sistem Informasi Universitas Atma Jaya Yogyakarta, 2021)
Software development comprises stages that are interrelated with one another. The analysis and design stages are the initial stages in software development. For novice software developers, diagram making as software modeling is something that can be done as an alternative in developing computer applications or systems. In this study, we carried the interface design for software modeling applications out. The application developed later is a web-based application as a solution to licensing problems and expensive software modeling tools. This study only focuses on application design, does not contain implementation and application testing. The method used in this research is a user-centered design method. This method was chosen because it uses the user as the center of the design. So we expect it that the design can adjust to the wants, needs, and needs of relevant users. After we have completed the design as a mockup, the next research is to implement and implement the applications that have been designed in this study based on the results of user feedback